Cyprus : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The COVID-19 pandemic has interrupted Cyprus's strong economic growth over the past few years. High dependence on service sectors and strict containment measures led real output to contract by 5.1 percent (yoy) during 2020. Growth is projected to recover to 3 percent in 2021 as the vaccine rollout gathers pace despite the ongoing new wave of infections, but significant downside risks remain, reflecting the high uncertainty of the path of the epidemic.